Pengaruh Penambahan Edible Coating Kitosan Rajungan (Portunus pelagicus) Terhadap Sensori Dodol Betawi - Pola Panjaitan; Reva Fiani; Aripudin Aripudin; Catur Pramono Adi; Liliek Soeprijadi (Jurnal Airaha, 2020)
The research objective was to determine the effect of the edible coating of crab chitosan on the sensory quality of Betawi dodol. The process of making crab chitosan edible coating starts from mixing chitosan, 1% acetic acid, and glycerol, immersing dodol into edible coating solution, and storage. Edible coating with a concentration of 4% chitosan (K3) can maintain appearance and texture values ​​until day 12 and aroma until day 16, longer than K0 and K1 treatments can only maintain appearance and texture values ​​until day 4 and aroma until the 8th day and K2 which can maintain the appearance and texture values ​​until the 8th day and the aroma until the 12th day and there is no difference in the taste values ​​in the three treatments. Based on the Friedman test, the parameters of appearance, aroma, and texture have a sig. <0.05 so that H1 is accepted and H0 is rejected, which means that the difference in chitosan concentration has a significant effect. Meanwhile, the Friedman taste test has a sig.> 0.05 so that H0 is accepted and H1 is rejected, which means that the difference in chitosan concentration does not have a significant effect.